ҚАРАҚАЛПАҚСТАНДАҒЫ ТҮРКИЙ ТИЛЛЕРДИҢ ӨЗ АРА ТӘСИРИ МӘСЕЛЕСИНИҢ ҮЙРЕНИЛИЎИ - Куртчаев, А.Т. (ILIM hám JÁMIYET, 2017)
The article deals with the study of lexical, phonetic, morphological changes in the result of intra-influence of languages of the Turkic people living in Karakalpakstan and speaking in Karakalpak, Uzbek, Turkmenian and Kazakh.